2015
DOI: 10.4049/jimmunol.1500447
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Preferentially Target Tumor Cells with a Cancer Stem Cell Phenotype

Abstract: Increasing evidence supports the hypothesis that cancer stem cells (CSCs) are resistant to antiproliferative therapies, able to repopulate tumor bulk, and seed metastasis. NK cells are able to target stem cells as shown by their ability to reject allogeneic hematopoietic stem cells but not solid tissue grafts. Using multiple preclinical models, including NK coculture (autologous and allogeneic) with multiple human cancer cell lines and dissociated primary cancer specimens and NK transfer in NSG mice harboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(178 citation statements)
references
References 36 publications
5
173
0
Order By: Relevance
“…These observations are in agreement with those previously reported in other human solid tumor experimental systems. [15][16][17]25 In Fig. 2, NK cells were activated with IL2 in vitro, whereas autologous and allogeneic NK cells were used as effectors without any activation in Table 1.…”
Section: Tumorspheres Derived From the Murine Erbb2mentioning
confidence: 99%
“…These observations are in agreement with those previously reported in other human solid tumor experimental systems. [15][16][17]25 In Fig. 2, NK cells were activated with IL2 in vitro, whereas autologous and allogeneic NK cells were used as effectors without any activation in Table 1.…”
Section: Tumorspheres Derived From the Murine Erbb2mentioning
confidence: 99%
“…14 Recently, increasing evidence from preclinical and clinical studies supports the potential efficacy of NK cell therapeutics in multiple cancer types. 15-19 Clinical studies also showed a positive correlation between outcomes of the therapy and the dose of NK cells administered, prompting the development of effective methods to grow NK cell in vitro . 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…22 NK cells expanded by the K562-mb21 feeder cell method are currently used in multiple clinical trials and preliminary results are showing highly encouraging clinical efficacy for leukemia relapse prevention after stem cell transplant. 15 Recently, the K562-mb21 cell based method was modified to a cell-free, PM21-particle based method for both ex vivo and in vivo specific expansion of NK cells which can eliminate some logistical and safety concerns while also retaining the benefits of the feeder-cell based expansion. 24,25 These significant breakthroughs made in regards to generating large doses of NK cells allow for their potential use as a viable and attractive therapeutic option for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…IL-2-and IL-15-activated NK cells were found to be cytotoxic against human breast cancer stem cells and CD 133+ melanoma CSCs [90]. Recently, Ames et al [91] showed that NK cells kill CSCs from diferent kinds of tumors, through the interaction of the NKG2D activating receptor with its ligand (MICA/B). …”
Section: Nk Cells Targeting Cancer Stem Cellsmentioning
confidence: 99%